Esports research and its integration in education - Harvey, Miles 1987-; Marlatt, Rick 1980- (A volume in the Advances in game-based learning (AGBL) book series, 2021)
"The world of esports in education is booming on an international scale, as evidenced by a proliferation of teams and competitions across numerous platforms such as Twitch, Discord, Youtube, and more, his book presents empirical studies to help us understand how esports is developing within and around learning institutions and what the impact may be on students and their contemporary educational experiences" - Provided by publisher